Landscapes of Privilege : Aesthetics and Affluence in an American Suburb. - Duncan, James (Routledge, 2003)
Focusing on an archetypal upper class American suburb, the authors look at how the aesthetics of physical landscapes are fully enmeshed in producing the American class system.